Activities related to sustainable development and environment (FAO RomeIT, 1993)
Reviews the major implications of UNCED and post-UNCED decisions at national, regional and international levels in the domains of concern to the organization. Presents an overview of FAO's response to UNCED and reviews a number of emerging issues and challenges which UNCED follow-up poses to FAO's member governments, and to the organizaiton. Makes a series of proposals for action by the Conference.
DC